Optimization of Personnel Management in Banks and Capacity Building Based on Foreign Experience - Abdurahmanov Alimardon Siddiqovich; Mirzaeva Shirin Nodirovna; Burkxonov Bekzod Saidazim o’g’li (International Journal on Economics, Finance and Sustainable Development, 2022)
This article deals with the management of banks and their capacity building on the basis of foreign experience, further optimization of the industry. Foreign experience in capacity building will also be considered.